Chronic Kidney Disease as a Long-term Consequence of Preeclampsia and Hypertensive Disorders in Pregnancy - Biljana Gerasimovska Kitanovska; Gerasimovska, Vesna (Walter de Gruyter GmbH/Macedonian Medical Association, 2016)
Preeclampsia is a condition characterized by hypertension, proteinuria after 20th week of gestation, dysfunction of other maternal organs or uteroplacentary dysfunction and is associated with short-term renal damage. Recent studies report on potential association of preeclampsia with chronic kidney disease in later life. The aim of this study was to determine this potential association by literature review and our results. Methods. A Pubmed (Medline) literature search on the association of preeclampsia and subsequent chronic kidney disease was carried out. Our study was conducted at the Department of Nephrology of the University Clinical Centre Skopje in 2010 and included women who consulted the Clinic due to hypertension or impaired renal function and who had either preeclampsia or hypertensive disorders in pregnancy. Thirty patients with decreased glomerular filtration that occurred 1-28 years after pregnancy with hypertensive disorder were included in the study. Results. Literature search yielded 227 abstracts, of which 19 papers were selected, and they referred only to chronic kidney disease in the period after delivery in patients with preeclampsia. Various risks for emergence of chronic kidney disease in later life were reported in recent literature, varying from 1.2 to 14 for preeclampsia and in patients with superimposed preeclampsia, the risk was 45 times higher. In our study, risk of reduction in glomerular filtration rate was highest in the first 5 years (OR 3.6, 95% CI 1.06-22.5). Delivery before 27 weeks of gestation insignificantly increased the risk of reduced glomerular filtration in the later period (OR 1.33 95% CI 0.2-8.5). Preeclampsia is not a direct risk factor for chronic kidney disease, however, proteinuria over 0.3 g/24h in the group of patients with hypertension or preeclampsia in pregnancy, increased the risk of reduced glomerular filtration rate by 28 times (OR 28.5, 95% CI 2.7-30.9). Conclusions. Patients with preeclampsia need careful monitoring in postpartal and long-term period, not only for cardiovascular but for chronic kidney disease.